COVID-19 Impact on the Lives of Diverse Populations: A Descriptive and Analytical Cross-Sectional Study - Ilyes Zatla; Lamia Boublenza; Ghouti Zatla; Zoubida Chikh (Masters Program in Public Health, 2023)
Background: SARS-CoV-2 is a highly pathogenic and transmissible respiratory virus that causes the COVID-19 disease, that has affected both our physical and mental health leaving scarring lesions on both. Our objective was to assess the impact of this virus on the social behavioral status of individuals and the acceptance of its impact.Subjects dan Method: A cross-sectional study was conducted from June 2021 to September 2021, using a questionnaire to collect data from random international study participants. Descriptive and statistical analysis were run on SPSS Statistics with a p-value <0.050.Results: Results obtained found that most of the participants (78.3%) followed the procedures to prevent the infection, few (25.8%) of the them have been infected or have at least confirmed the infection with COVID-19 tests, but also few of these partakers (40.4%) have been vaccinated.Conclusion: The pandemic and its surrounding rumors about the virus or COVID-19 vaccines never fail to affect day-to-day life. The disease and its post-complications had/still surround many enigmas for our physical and mental health and the return to normal would be even harder. Keywords: COVID-19, SARS-CoV-2, Impact, Pandemic, Survey. Correspondence: Ilyes Zatla. Laboratory of Microbiology applied to the Food industry, Biomedical and the Environment, Faculty of Natural and Life Sciences, Earth and Universe Sciences. Department of Biology. University of Tlemcen, Algeria. Email: ilyes.zatla@univ-tlemcen.dz. Mobile: +213540315422.